Kulturtransfer und Lehrüberlieferung Moritz Steinschneider (1816-1907) und “Die Juden als Dolmetscher” - Endress, Gerhard (Oriens, 2011)
Abstract Cultural transfer and teaching tradition: Moritz Steinschneider and “The Jews as Interpreters.” — The œuvre of Moritz Steinschneider was planned as part of a monumental project, to present the interrelations between the Jewish, Muslim and Christian communities “in regard of religion, literature and cultural history” in their entirety. It has become a habit to label Steinschneider as the “Father of Hebrew bibliography”, whose work can safely be used as a quarry, but could be much better continued with the help of modern information technology. Indeed, bibliography — notably the description, identification and evaluation of thousands of Hebrew and Judæo-Arabic manuscripts — is the basis of his, and of all further work in the field. But on this basis, Steinschneider unfolded the interrelation and interchange of the epistemic community of the Mediterranean, between Palestine, Mesopotamia, and Iran, between Egypt, Andalusia, Italy and the Provence; through his work, a continuous chain of teaching, interpretation and translation has been brought to life, manifold in language, in religious and intellectual orientation, committed to tradition, but open to innovation: “Für den Geist gibt es kein Ghetto!”